2017
DOI: 10.1017/s1463423617000780
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of sexual healthcare provided by school nurses

Abstract: Following a review of the literature, a mixed methods study was undertaken which included an audit of documentary data to identify the referrals received in relation to sexual health and also included questionnaire surveys of school staff and SNs on their views of the role of the SN in sexual health.FindingsSNs and school staff identified that SNs have a role in sexual health, which was reflected in the referrals received during the audit of documentary data. There appeared to be inconsistencies across the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(36 reference statements)
0
3
0
3
Order By: Relevance
“…School nurses are community health nurses that specialize in working with the school-aged children to enhance their health and well-being and are thus in a unique position to promote the sexual health of children and adolescent. These nurses play an important role in sexual health by developing schoolbased health services, and providing sex and relationships education (Beech & Sayer, 2018).…”
Section: Relevant (Unicef and Ministry Of Education 2016)mentioning
confidence: 99%
“…School nurses are community health nurses that specialize in working with the school-aged children to enhance their health and well-being and are thus in a unique position to promote the sexual health of children and adolescent. These nurses play an important role in sexual health by developing schoolbased health services, and providing sex and relationships education (Beech & Sayer, 2018).…”
Section: Relevant (Unicef and Ministry Of Education 2016)mentioning
confidence: 99%
“…El periodo de tiempo realizado fue desde el 4 de junio 2020 hasta el 18 Esto dio un total de 247 artículos por título de los cuales fueron seleccionados 96 artículos por resumen. Las autoras leyeron los 96 artículos a texto completo, descartando 63 artículos porque no tenían relación con los objetivos de la revisión sistemática, eligiendo 32 artículos que sí tenían relación con los objetivos establecidos.…”
Section: Métodosunclassified
“…Prosiguiendo con el quehacer educacional, uno de los aspectos más relevantes que se encuentran en los artículos es la educación temprana de las enfermedades de transmisión sexual en los escolares, teniendo su énfasis sobre todo en la etapa de la adolescencia. En un estudio realizado por Beech et al (18) , en Londres, con el objetivo de explorar el papel y las actividades del servicio de enfermería escolar en salud sexual, las derivaciones de embarazos de adolescentes sugieren un apoyo por parte del servicio de enfermería escolar. De las derivaciones recibidas, solo el 15% fueron de sexo masculino y el 85% de estas se relacionaban con un problema en el uso de preservativo como método anticonceptivo.…”
Section: Competencias Y Acciones Del Profesional De Enfermería En Los Establecimientos Educacionalesunclassified
“…Positive communication between adolescents and parents and/or parental participation in school-based education have produced multiple positive outcomes, including more positive attitudes toward abstinence [9], safer sexual behaviors [24], decreased risk of multiple sex partners [25] and postponement of vaginal sex [18]. Public health nurses (PHNs) (or "school nurses") have long been involved in sexual health promotion in school settings, although the most common student access is through referral [26]. Evaluations of PNH roles have suggested that more active involvement is needed [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Public health nurses (PHNs) (or "school nurses") have long been involved in sexual health promotion in school settings, although the most common student access is through referral [26]. Evaluations of PNH roles have suggested that more active involvement is needed [26,27]. Most PHNs advocate comprehensive sex education programs [28].…”
Section: Introductionmentioning
confidence: 99%